(untitled) (Advancements in Homeopathic Research, 2023)
Respiratory tract infection is the most common infection worldwide in recent years which affect children frequently. This is mainly classified into upper respiratory tract infection and lower respiratory tract infection. Recurrent upper respiratory tract infection means defined as six or more than six serious attacks of symptoms of respiratory tract for minimum 1 year which will affect normal functioning. Asthma is a common public health problem around worldwide developed countries. About 300 million people have been affected globally due to bronchial asthma. Homoeopathy is a system which treats patients with individual symptoms by various methods of homoeopathic prescription to attain an exact cure.